Majority-layered T hybridization using quantum-dot cellular automata. Issue 1 (1st January 2017) - Mukherjee, Chiradeep; Panda, Saradindu; Mukhopadhyay, Asish Kumar; Maji, Bansibadan
Abstract: The atomistic quantum-dot cellular automata (QCA) based implementations of the reversible circuits have got tremendous exposures in the last few days, due to "room-temperature workability" of the QCA. The researchers are in serious need of a methodology that can realize the area-efficient QCA counterparts of reversible benchmark circuits. In this work, a novel methodology named majority-layered T hybridization is proposed to synthesize the reversible circuits using QCA. Firstly the reversible library consisting of CNTS Gates have been generated to validate the usability of the proposed methodology. Then, an elementary QCA module of 3×3 Toffoli Gate have been proposed and extended in the realization of 4×4, 5×5 and 6×6 Toffoli Gates (multi-control Toffoli Gates). The proper mathematical modelling of the several QCA design metrics like effective area, delay and O-cost has been established. The QCA counterpart of 3×3 Toffoli Gate reports 18.61% less effective area and 8.33% less O-cost compared to the previous Toffoli Gate designs. Moreover, the QCA layout of rd - 32 reversible benchmark using multi-control Toffoli Gate has been employed to verify the scalability and reproducibility of the proposed methodology. The QCA layouts are generated, tested and simulated by renowned computer aided design tool QCADesigner 2.0.3.